Prevalence and factors associated with restless legs syndrome among pregnant women in middle-income countries: a systematic review and meta-analysis - Mislu, Esuyawkal; Assalfew, Betel; Arage, Mulugeta Wodaje; Chane, Fiker; Hailu, Tilahun; Tenaw, Lebeza Alemu; Kidie, Atitegeb Abera; Kumsa, Henok (Frontiers in Medicine, 2023)
Introduction Restless legs syndrome (RLS) is a debilitating condition characterized by uncomfortable sensations in the legs, typically occurring during periods of rest or sleep. It is more prevalent during pregnancy and is linked to sleep disturbances, diminished quality of life, and pregnancy complications. However, previous studies yielded inconsistent findings among pregnant women in middle-income countries. Consequently, this systematic review and meta-analysis sought to determine the pooled prevalence of restless legs syndrome and its associated factors in these populations. Method A systematic review and meta-analysis was conducted on published studies from middle-income countries until May 2023. The review strictly adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Relevant search terms were used to search for studies in PubMed, MEDLINE, EMBASE, and Google Scholar. Data extraction was performed using the Joanna Briggs Institute tool for prevalence studies. The meta-analysis was conducted using STATA 17 software, and heterogeneity was assessed using the I2 test, while publication bias was evaluated using Egger's test. Forest plots were also used to present the pooled prevalence and odds ratio (OR) with a 95% confidence interval (CI) using the random-effects model. Result This review included 22 studies from nine countries with a total of 17, 580 study participants. The overall pooled prevalence of RLS among pregnant women in middle-income countries was 13.82% (95% CI: 13.31, 14.32), and having low hemoglobin level (AOR: 1.68, 95% CI: 1.29, 2.18), history of RLS (AOR: 7.54, 95% CI: 3.02, 18.79), muscle cramps (AOR: 3.58, 95% CI: 1.21, 10.61), excessive day time sleepiness (AOR: 4.02, 95% CI: 1.34, 12.04), preeclampsia (AOR: 2.06, 95% CI: 1.28, 3.30), and taking prophylactic iron supplementation (AOR: 0.59, 95% CI: 0.50, 0.69) were the identified factors associated with it. Conclusion Generally, nearly one in every eight pregnant women in middle-income countries develop restless legs syndrome during pregnancy. Having low hemoglobin level, a history of RLS, muscle cramps, excessive daytime sleepiness, preeclampsia, and taking prophylactic iron supplementation were the identified factors associated with it. These findings underscore the importance of addressing the identified factors associated with RLS in order to effectively mitigate its occurrence among pregnant women.